PENERAPAN MODEL PEMBELAJARAN CONNECTING ORGANIZING REFLECTING EXTENDING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII - Asifa, Putri (Jurnal Edukasi dan Penelitian Matematika, 2023)
The ability to understand mathematical concepts is one of the important learning objectives to be mastered by students. However, in reality the ability to understand mathematical concepts in class VIII students of SMP Negeri 1 Tanah Putih, Rokan Hilir Regency, is still relatively low. To overcome this problem, one way that can be done is to apply the Connecting Organizing Reflecting Extending learning model. The purpose of this study was to find out whether the ability to understand mathematical concepts of students who studied with the Connecting Organizing Reflecting Extending learning model was better than those who studied with the direct learning model in class VIII SMP Negeri 1 Tanah Putih, Rokan Hilir Regency. This type of research is a quasi-experimental design with the nonequivalent posttest-only group design. The population is all students of class VIII SMP Negeri 1 Tanah Putih, Rokan Hilir Regency with a sample of class VIII.2 and VIII.3. The instrument used is the final test of the ability to understand mathematical concepts. Keywords- Ability To Understand Mathematical Concepts, Connecting Organizing Reflecting Extending, Direct Learning